INTERPRETASI BAWAH PERMUKAAN DAERAH SUMBER AIR PANAS DIWAK-DEREKAN BERDASARKAN DATA MAGNETIK - Muhammad Ulin Nuha ABA; Tony Yulianto; Udi Harmoko (Youngster Physics Journal, 2014)
Research has been carried out using a magnetic method that aims to interpret the subsurface structure of the area hot springs Derekan - Diwak based on the total magnetic field anomaly data. It also aims to investigate the geothermal system in the area.Some 99 points measurement areas were measured using PPM (Proton Precession Magnetometer) geometrics type GSM19T models to get the value of the total magnetic field and two points as a base station simultaneously measured using the PPM G856X models. Measurement data is processed by the daily variation correction and IGRF (International Geomagnetic Reference Field) correction. The data has been used to create a contour corrected total magnetic field anomalies and subsurface cross sections involving the upward continuation and reduction to the poles.The results of study showed the total magnetic field anomaly closure pair of positive and negative closure indicate a fault zone below the surface. Interpretation is strengthened by the results of the modeling showed two faults of Derekan - Diwak areas trending southwest- northeast. This fault zone is a media outlet fluid to the surface in the area of geothermal systems.Keywords: geothermal, fault, and total magnetic field